Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1108/gm-06-2013-0063
|View full text |Cite
|
Sign up to set email alerts
|

Patriarchal paradox: gender performance and men's nursing careers

Abstract: Purpose – In this paper, the authors situate existing scholarship about men in nursing within the broader gendered landscape of the profession and society. As a consequence, the need to reframe the discourse about men in nursing from the current emphasis on personal or collective experiences to collective action becomes apparent. The paper aims to discuss these issues. Design/methodology/approach – A critical synthesis of scholarship addressing men in nursing serves as the basis for a conceptual paper whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 40 publications
6
27
0
Order By: Relevance
“…Instead of conforming, some men may choose non‐nursing professions which may partially account for persistently low numbers of men in nursing. This study confirmed findings in the literature about social stigmas and sex‐based stereotypes affecting men in nursing (Kellett et al, ; Kouta & Kaite, ; Roth & Coleman, ; Weber, ). The persistence of these stereotypes implies that social stigmas do not end easily and will probably continue to deter men.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Instead of conforming, some men may choose non‐nursing professions which may partially account for persistently low numbers of men in nursing. This study confirmed findings in the literature about social stigmas and sex‐based stereotypes affecting men in nursing (Kellett et al, ; Kouta & Kaite, ; Roth & Coleman, ; Weber, ). The persistence of these stereotypes implies that social stigmas do not end easily and will probably continue to deter men.…”
Section: Discussionsupporting
confidence: 90%
“…Cultural and sex‐based norms defining masculinity lead to preconceptions of what compassion looks like. Sex‐based definitions of masculinity reinforce the stereotypes that negatively affect men in nursing (Kellett et al, ). Caring is a complex concept and there are no rules that dictate which sex is qualified to care or have compassion (Perry, ; Zhang & Liu, ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Yet, men's privilege is complicated by intersections of social difference such as race, class and sexuality (Brown, 2009;Lupton, 2006;Williams, 1995;Wingfield, 2009Wingfield, , 2010. Additionally, feminized occupations present their own unique challenges to men, as gendered expectations on the job may be difficult to negotiate (Kellett et al, 2014;Lupton, 2000). Care work as a whole is stereotyped as feminine and associated with women and gay men, an association which may be especially harmful to men personally and professionally (Blashill and Powlishta, 2009;Hicks, 2006;Willis et al, 2011).…”
Section: The Heteronormative Labour Of Caringmentioning
confidence: 99%